Time-course of changes in oxidative stress and antioxidant status responses following a soccer game - Fatouros, I. G.; Ghatzinikolaou, A.; Douroudos, I. I.; Nikolaidis, M. G.; Kyparos, A.; Margonis, K.; Michailidis, Y.; Vantarakis, A.; Taxildaris, K.; Katrabasas, I.; Mandalidis, D.; Kouretas, D.; et al. (The Journal of Strength and Conditioning Research, 2010)
Exercise-induced muscle damage is associated with an acute-phase inflammatory response characterized by phagocyte infiltration into muscle and free radical production. Although soccer includes intense eccentric muscle actions that cause muscle damage, the oxidative stress responses after a soccer game are currently unknown. The present investigation attempted to determine the responses of circulating levels of oxidative stress and antioxidant status markers during recovery from a soccer game. Twenty soccer players (experimental group) were assigned to 2 different teams that competed against each other (2 × 45 minutes). Ten other players served as controls (rested). Creatine kinase (CK) activity, uric acid, leukocyte count, malondialdehyde (MDA), protein carbnyls (PC), reduced (GSH) and oxidized glutathione (GSSG), antioxidant capacity (TAC), catalase, glutathione peroxidase activity (GPX), delayed-onset of muscle soreness (DOMS), and anaerobic performance (speed, vertical jump performance) were measured before and following (immediately post, 24 hours, 48 hours, 72 hours) the game. Performance deteriorated (2-17%, p < 0.05) throughout recovery. Leukocytosis developed (p < 0.05) immediately following the game and at 24 hours. Both CK and DOMS (3-8-fold, p < 0.05) increased from baseline and remained elevated (p < 0.05) through 48 hours. Thiobarbituric acid reactive substances (TBARS), PC, uric acid, GPX, and TAC increased (13-67%, p < 0.05) throughout recovery, whereas catalase was elevated (38%, p < 0.05) only immediately after the game. GSH/GSSG declined (17-75%, p < 0.05) throughout recovery. Our results suggest that oxidative stress is markedly upregulated by a soccer game, probably as a part of the exercise-induced inflammatory response, and is accompanied by a marked deterioration of anaerobic performance for as long as 72 hours.